The Effect Of Focus Error And Spherical Aberration On Sharp Edge Image Intensity - Safaa Mustafa Hameed (Tikrit Journal of Pure Science)
This research has been carried out to determine the distribution of the intensity in the image of object with a Sharp-Edge using coherent illumination. In this research, a special formulas have been derived called the Edge spreads Function (ESF) .This formula is very useful for theoretical and practical studies since it is applicable to system with any kind and amount of aberrations that are present in the optical systems by using pupil function technique.